Chemokines and Chemokine Receptors: Accomplices for Human Immunodeficiency Virus Infection and Latency - Wang, Zhuo; Shang, Hong; Jiang, Yongjun (Frontiers in Immunology, 2017)
Chemokines are small chemotactic cytokines that are involved in the regulation of immune cell migration. Multiple functional properties of chemokines, such as pro-inflammation, immune regulation, and promotion of cell growth, angiogenesis, and apoptosis, have been identified in many pathological and physiological contexts. HIV infection is characterized by persistent inflammation and immune activation during both acute and chronic phases, and the "cytokine storm" is one of the hallmarks of HIV infection. Along with immune activation after HIV infection, an extensive range of chemokines and other cytokines are elevated, thereby generating the so-called “cytokine storm”. In this review, the effects of the up-regulated chemokines and chemokine receptors on the processes of HIV infection are discussed. The objective of this review was to focus on the main chemokines and chemokine receptors that have been found to be associated with HIV infection and latency. Elevated chemokines and chemokine receptors have been shown to play important roles in the HIV life cycle, disease progression, and HIV reservoir establishment. Thus, targeting these chemokines and receptors and the other proteins of related signaling pathways might provide novel therapeutic strategies, and the evidence indicates a promising future regarding the development of a functional cure for HIV